Warisan Kejayaan Madinah bagi Pengembangan Kajian Ilmu Sosial dan Politik - Jatmika, Sidik (Universitas Muhammadiyah Yogyakarta, 2013)
Besides giving ethic things, the glory of Madinah also gives some ideas, concept and perspective on social and political sciences for the future. What shows in the Muhammad prophet leadership in the Madinah period was given precious contribution on Khazanah social and political sciences which developing. Various of law, ethics, even recent ideas had historic roots in Madinah era.